Partição da evapotranspiração, rendimento de grãos e retorno econômico da soja cultivada sob diferentes estratégias de irrigação - Báez, María Soledad Armoa (2017)
Irrigation strategies that promote water savings are needed in current and future scenarios for various locations around the world. Poor irrigation appears as an alternative to contribute to this, reducing the impacts on production when applied during less sensitive phases of crop development. The precise determination of water losses in the soil-plant-atmosphere system in the form of crop evapotranspiration (ETc) guarantees a better irrigation water management, thus, it is worth noting the utility of simulation models such as SIMDualKc, which due to methodology implemented by it, favors the partitioning of ETc in its base components, crop transpiration (Tc) and soil evaporation (Es). This study aimed to evaluate the dynamics of the water balance and the impacts of water stress on the water productivity and soybean crop yield with crop residues on the soil surface in order to generate an irrigation strategy that reduces water use and optimizes water and crop productivity in the sub-humid climatic conditions of Santa Maria, RS, during the 2016 crop season. The experiment was conducted inside a rain shelter, where 4 treatments with different levels of water stress were tested: T1 (no water stress), T2 (mild water stress), T3 (moderate water stress) and T4 (severe water stress). A completely randomized experimental design with 3 replications was implemented. Irrigation was performed with a micro- sprinkler system when soil moisture reached 80, 70, 60 and 50% of the total available water (TAW). The soil was content was monitored at the entire soil profile till 0.85 m throughout the crop development cycle with FDR sensors. The ETo was daily calculated by the Penman-Monteith method using meteorological data registered at the INMET (Instituto Nacional de Mateorologia) automatic station, located 200 m from the experimental area. The results demonstrate that the SIMDualKc model was sufficiently able to simulate the variation of the available soil water during the soybean development cycle, and consequently determine the water balance. The Kcb values calibrated and validated for the soybean crop demonstrate the high accuracy of the simulations. Due to the high atmospheric demand at the start of the experiment, the evaporation component of the soil represents, on average, 28% of the observed ETc. It can be concluded that T1 treatment may be the best option to obtain the highest crop grain yield, while T4 treatment is a better option due to the increase in water productivity, producing more with less soil available water.